Parallels of structural-functional parameters the myocardium, C-type natriuretic peptide and endothelin-1 plasma concentrations in women with uncomplicated essential hypertension - V. V. Petrovska; B. M. Zhebel (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
The development of endothelial dysfunction (DE)plays an important role in the pathogenesis of essential hypertension (EH). Processes of vascular wall remodeling (hyperplasia and hypertrophy of smooth muscle cells of the media, fibrosis) cause progression and stabilization of arterial hypertension [7] and lead to the development of cardiac dysfunction with its subsequent remodeling. From this point of view the study of plasma concentrations of vasodilator-natriuretic peptide C and its direct antagonist endothelin-1 is an important task.